(untitled) (Washington, D.C., 1997)
This book will be important to anyone concerned about the future of agriculture: policymakers, regulators, scientists, farmers, educators, students, and suppliers to the agricultural industry.
Keywords: Precision farming,Nông nghiệp chính xác